Development of Interactive Learning Media Based on a 2-Dimensional Virtual Laboratory on Electrochemical Materials - Joko, Neneng Andriani; Rudi, La; Arsyad, Muhammad (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to analyze the feasibility of interactive learning media based on a 2D virtual laboratory for electrochemistry material and to examine students' responses to its use. The media was designed as a solution to address the limitations of laboratory equipment and materials often encountered in schools. The research method employed was Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The media’s validity was analyzed using Aiken’s V content validity, involving three expert validators. The results of the analysis indicated a validity score of 0.86, which falls into the high category, demonstrating that the media is feasible for use. Student responses to the media were also analyzed, yielding an overall quality percentage of 75.98%, classified as good. Based on these findings, the learning media is considered effective and applicable in the teaching and learning process for electrochemistry materials to enhance students' conceptual understanding and practical skills.